Influencia del Lecho Marino, en el Transporte de Energía Undimotriz Transmitida por las Olas. (2011)
The energetic overview in the world has originated the constant search of strategies to cover the energy demand. In this way, renewable energy sources have been studied and among them the wave energy, which is studied in this paper. Starting from other investigations on this topic, the seabed is seen as an element that is involved in energy obtention, which has encouraged in this work to the elaboration of four different models of seabed (horizontal smooth, horizontal undulated, tilted smooth and tilted undulated bed), that are easy to develop in several projects aimed to analyze their incidence on energy transport through waves.  This is the reason why a glass bucket was calculated in order to stand the mass water and the stresses caused by additional elements; a device for driving the wind column that was applied to the mass water was also developed. In the same way, deformation of a membrane located at the end of the bucket was measured using images of the membrane deformation, in such a way that when there is more energy, the deformation is greater. The deformation measurement was carried out using a digital image processing program to obtain two descriptors: the equivalent diameter (the distance between the center of the image that contains the deformed membrane and the most external point of the image), and the equivalent area (the area of the deformed membrane image). In this way the descriptors that present a higher value indicate a greater membrane deformation and therefore a favorable influence on the seabed that is the only changing element. When applying the program to 69 photo-frames, the results showed the tilted undulated bed as the more favorable condition regarding wave energy transport.